Evaluation of factors associated with fear to fall in the adult major institutionalized (Revista horizonte, 2022)
Objective: To determine the regression model of the fear of falling syndrome in the institutionalized older adult. Methodology: An explanatory study was designed. 32 subjects from the Siervas de Jesús center in the city of Talca participated. The covariates of lower limb muscle strength, dynamic stability, cognitive ability, depression, risk of falling and self-perception of physical independence were evaluated. The model was determined by binary logistic regression, in all cases a p 1), with muscle weakness being the variable most important (OR = 3.0). The rest of the covariates presented the following parameters: dynamic stability (OR = 1.8), cognitive ability (OR = 1.1), depression (OR = 1.5), risk of falling (OR = 2.5) and self-perception of physical independence (OR = 2.3). The model had a determination coefficient of 80% (R2 = 0.80). Conclusion: The probability of developing the fear of falling syndrome in the institutionalized older adult increases by 3 times due to a reduction in the muscle strength of the lower limb adjusted for the presence of instability, cognitive decline, depression, risk of falling and physical dependence of the subjects.